"PROBLEMS OF EDUCATION QUALITY IN THE PROCESS OF IMPLEMENTING DIGITAL TECHNOLOGIES IN THE MODERN EDUCATION SYSTEM" (Universal International Scientific Journal, 2026)
This article analyzes the process of introducing digital technologies into the modern education system. Digital technologies are considered an important tool for increasing the efficiency of education, individualizing knowledge acquisition, and optimizing the educational process. At the same time, problems such as insufficient technical infrastructure, low digital competence of teachers, underdeveloped assessment and monitoring systems, poor quality of educational content, and the digital divide negatively affect the quality of education. The article emphasizes the need for a scientifically based analysis of these problems and comprehensive approaches to their elimination.
Keywords: Modern education, digital technologies, quality of education, pedagogical competence, digital divide, online education, educational content, educational monitoring